IMPLEMENTATION OF EDUPRENEURSHIP: A LEADING PROGRAM IN THE FORM OF ACADEMIC GUIDANCE AT SDIT AL HUSNA - Andriani, Putri (Universitas Labuhanbatu, 2024)
21st century learning demands adaptation of education to prepare students for global challenges and evolving technology. The Merdeka curriculum in Indonesia provides freedom to schools and students in determining the learning process that suits local needs. This study aims to assess the implementation of the edupreneurship-based academic guidance program at SDIT Al Husna, which includes deepening subject matter and developing independent learning skills. The method used was descriptive qualitative with data collection through observation. The results showed that this program succeeded in improving students' academic achievement with an average score increase of 20% in Mathematics, Science, and English subjects. In addition, the program also developed students' soft skills and entrepreneurial spirit through practical activities. Despite challenges in implementation, corrective measures can increase the effectiveness of the program. This study recommends the application of edupreneurship principles as a model for other schools in improving the quality of education and students' skills to face future challenges.Keywords: Implementation; Edupreneurship; Academic GuidanceAbstrak Pembelajaran abad ke-21 menuntut adaptasi pendidikan untuk mempersiapkan siswa menghadapi tantangan global dan teknologi yang terus berkembang. Kurikulum Merdeka di Indonesia memberikan kebebasan kepada sekolah dan siswa dalam menentukan proses pembelajaran yang sesuai dengan kebutuhan lokal. Penelitian ini bertujuan untuk menilai pelaksanaan program bimbingan akademik berbasis edupreneurship di SDIT Al Husna, yang mencakup pendalaman materi pelajaran dan pengembangan keterampilan belajar mandiri. Metode yang digunakan adalah kualitatif deskriptif dengan pengumpulan data melalui observasi. Hasil penelitian menunjukkan bahwa program ini berhasil meningkatkan prestasi akademik siswa dengan rata-rata nilai meningkat sebesar 20% pada mata pelajaran Matematika, IPA, dan Bahasa Inggris. Selain itu, program ini juga mengembangkan soft skills dan jiwa kewirausahaan siswa melalui kegiatan praktis. Meskipun terdapat tantangan dalam implementasi, langkah-langkah perbaikan dapat meningkatkan efektivitas program. Penelitian ini merekomendasikan penerapan prinsip-prinsip edupreneurship sebagai model bagi sekolah lain dalam meningkatkan kualitas pendidikan dan keterampilan siswa untuk menghadapi tantangan masa depan.Kata Kunci: Implementasi; Edupreneurship; Bimbingan Akademik